Determination of the Best Controlled-Release Potassium Chloride and Fulvic Acid Rates for an Optimum Cotton Yield and Soil Available Potassium - Geng, Jibiao (Front Plant Sci, 2020)
Potassium and fulvic acid (FA) fertilizer applications are two important measures for improving cotton growth. However, there are few studies on the application interactive effects of controlled-release potassium chloride (CRK) in combination with FA on cotton production. To explore the effects of CRK combined with FA on cotton, field experiments were conducted in 2018 and 2019 using a split-plot design. The main plots were assigned to two types of potassium fertilizer – controlled-release potassium chloride (CRK) and potassium sulfate (KS) – while low, moderate, and high FA application rates (90, 180, and 270 kg ha(−1)) were assigned to the subplots. The cotton yield, fiber quality, net profit, soil available potassium concentration, potassium use efficiency, and leaf photosynthesis were markedly affected by potassium fertilizer and FA. The cotton boll number and boll weight in the 2 years and the yield in 2019 were all affected by the interaction between potassium fertilizer and FA. Compared to the other potassium treatments, the CRK × FA180 treatment increased the seed yield and net profit by 4.29–14.92% and 13.72–62.30%, respectively, over the 2 years. The potassium agronomy efficiency and potassium recovery efficiency (KRE) of the CRK × FA180 treatment were also improved by 6.25–30.77% and 3.82–12.78% compared to those of the other potassium treatments. Overall, the FA180 treatment resulted in better cotton growth than that in the FA90 and FA270 treatments. The release period of CRK in the field during the growth period of cotton was longer than that detected by 25°C static water extraction, which increased the soil available potassium content and met the potassium demands over the whole cotton growth period. Therefore, the application of CRK in combination with 180 kg ha(−1) FA is the best choice for cotton fertilization.